Arqueologia medieval em Portugal : 25 anos de investigação - Fernandes, Isabel Cristina Ferreira (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
This paper presents a state of the art on medieval archaeology in Portugal, concerning the last 25 years. The importance of the studies on ceramics and castles is underlined as well as the role of some publications to the development of the research. It also includes some statistical data and a view on the evolution of the university teaching of medieval archaeology.